Profil Pemecahan Masalah Matematika Siswa Kelas VIII SMP dengan Kecerdasan Intrapersonal dan Interpersonal - Agung Wicaksono; Mohammad Rizal; Sukayasa Sukayasa (Mitra Sains, 2019)
This study is a qualitative research that aims to get a description of the profile of mathematical problem solving class VIII SMP with intrapersonal and interpersonal intelligence based on Polya phase. The subjects of this study were students at grade eighth of Junior High School who have a intrapersonal and interpersonal intelligence. This study was conducted at the Junior High School in Palu, Central Sulawesi. The results of the study were as follow a) at the time to understand the math problems, subject who have intrapersonal intelligence tend to be cautious and be very confident if it had understood the problem well , while subject who have interpersonal intelligence tend to build up interaction with other people to easily understand the problems; b) during design the problem solving plan, both of the subjects used a same method, subjects with intrapersonal intelligence are relatively more patient and calm in the search for solving ideas than subject with interpersonal intelligence; c) when implemented problem solving plan, both of the subjects used the solving steps according to the plan, subject with intrapersonal intelligence did with relatively more thorough and careful than subject with interpersonal intelligence; d) when look back at the solution obtained, subject with intrapersonal intelligence tend to check repeatedly until feel confident with the answers, while subject with interpersonal intelligence tend to be checked only once and often asked and always said, had been convinced by the answer as to avoid having to prove in writing .